Mobilizing private finance for coastal adaptation: A literature review. (27th February 2018) - Bisaro, Alexander; Hinkel, Jochen
Abstract : Coastal adaptation can reduce climate change impacts and investing now, though costly, will bring greater benefits over the longer term, particularly in urban areas. Yet public actors currently cover a small fraction of needed coastal adaptation investments, a finance gap set to widen as coastal adaptation costs continue to increase. Mobilizing private finance for coastal adaptation is thus a salient challenge, as emphasized in the Paris Agreement. Key under‐researched dimensions of this challenge are what promotes private investment in coastal adaptation and how can public actors' interest in adaptation be aligned with private investor interests. To address this, we review the literatures on coastal adaptation finance and on financial arrangements involving both public actors and private investors. We describe key actors and interests, and identify coastal financial arrangements that align public actor and private investor interests, finding that private provisioning, public–private Partnerships (PPP), and public debt arrangements are promising. We then survey empirical examples, finding that private provisioning attracts investment when returns are high, for example, in urban real estate, and that PPPs attract dredging and construction companies' investment, particularly for adaptation measures with a large share of operational costs, for example, beach nourishment. We find little evidence of institutional investment through public debt instruments. A number of policy instruments, for example, concessional loans, tax incentives, and standards, may address this gap and enhance private coastal adaptation investment. Our results are also relevant for other sectors that involve long‐term infrastructure adaptation measures. This article is categorized under: Climate Economics > Iterative Risk‐Management Policy Portfolios Vulnerability and Adaptation to Climate Change > Learning from Cases and Analogies Abstract : Coastal adaptation finance arrangements: aligning public and private interests to mobilize private investment.